Effect of COVID-19 pandemic on outcomes in intracerebral hemorrhage - Daryl C. McHugh; Anna Gershteyn; Christine Boerman; Robert G. Holloway; Debra E. Roberts; Benjamin P. George (PLoS ONE, 2023)
Objectives Patients with severe intracerebral hemorrhage (ICH) often suffer from impaired capacity and rely on surrogates for decision-making. Restrictions on visitors within healthcare facilities during the pandemic may have impacted care and disposition for patient with ICH. We investigated outcomes of ICH patients during the COVID-19 pandemic compared to a pre-pandemic period. Materials and methods We conducted a retrospective review of ICH patients from two sources: (1) University of Rochester Get With the Guidelines database and (2) the California State Inpatient Database (SID). Patients were divided into 2019–2020 pre-pandemic and 2020 pandemic groups. We compared mortality, discharge, and comfort care/hospice. Using single-center data, we compared 30-day readmissions and follow-up functional status. Results The single-center cohort included 230 patients (n = 122 pre-pandemic, n = 108 pandemic group), and the California SID included 17,534 patients (n = 10,537 pre-pandemic, n = 6,997 pandemic group). Inpatient mortality was no different before or during the pandemic in either cohort. Length of stay was unchanged. During the pandemic, more patients were discharged to hospice in the California SID (8.4% vs. 5.9%, p<0.001). Use of comfort care was similar before and during the pandemic in the single center data. Survivors in both datasets were more likely to be discharged home vs. facility during the pandemic. Thirty-day readmissions and follow-up functional status in the single-center cohort were similar between groups. Conclusions Using a large database, we identified more ICH patients discharged to hospice during the COVID-19 pandemic and, among survivors, more patients were discharged home rather than healthcare facility discharge during the pandemic.